Lithofacies controls on gas accumulation in tight sandstone reservoirs: insights from the Permian Shihezi formation, south-western Ordos Basin, China - Xiaoming Wu; Xiaoming Wu; Zhongbin Chen; Zhicheng Shen; Yanxin Bao; Zheng Lan; Puxin Liu; Luxing Dou; Zhigang Wen (Frontiers in Earth Science)
IntroductionDeep tight sandstone reservoirs exhibit significant heterogeneity in both reservoir quality and gas-bearing properties. Although research on the quality of tight sand-stone reservoirs has been relatively thorough, the relationship between the sedimentary-diagenetic-hydrocarbon accumulation processes experienced by different lithofacies and their gas-bearing properties remains to be further explored.MethodsThis study focuses on the deep tight reservoirs of the He 8 Member of the Permian Shihezi Formation in the Huanjiang area of the Ordos Basin. By utilizing core samples, well logging data, and laboratory analysis, the basic characteristics of reservoir lithofacies were first analyzed. Subsequently, the distribution patterns of tight gas reservoir quality were clarified, and the controlling effects of sedimentary-diagenetic-hydrocarbon accumulation processes on gas-bearing properties were further investigated.ResultsThe study reveals that the He 8 Member reservoirs develop seven types of lithofacies, which can be categorized into two major groups: coarse-grained and fine-grained lithofacies. The overall porosity and permeability of the He 8 Member tight reservoirs are low, indicating dense reservoirs.DiscussionDue to significant differences in diagenetic processes between coarse-grained and fine-grained lithofacies, the coarse-grained lithofacies exhibit better physical properties. The fluid inclusion data suggest that natural gas may have preferentially migrated into coarse-grained, favorable lithofacies zones during the charging period, when the reservoirs were likely already in a relatively compacted state. This possible migration pattern could potentially lead to some degree of correlation between gas-bearing properties and reservoir quality, though further evidence is needed to confirm this relationship. The heterogeneity in gas-bearing properties of tight reservoirs is primarily controlled by the combined effects of lithofacies composition and structure, diagenetic processes, and the history of natural gas charging. This study proposes a geological model for the development of gas-bearing geological sweet spots controlled by favorable lithofacies. The sweet spot model has been validated through exploration practices and has guided the discovery of industrial gas flow wells.